Monitoring a trans-border labour market in view of liberalization - the case of Ticino - Siegfried Alberton; Oscar Gonzalez (European Regional Science Association (ERSA), 2004)
Switzerland has signed a treaty with the EU on free mobility. Beginning from the month of June 2004, this will replace the actual regulation based on quotas of foreign labor force and will facilitate the entrance of the Italian enterprises in the Ticino market. The evidence found when monitoring the Ticino economy for the period 1980 to 2002, is that the opening of the market has largely been anticipated and the regional economies, north and south of the border, seem to be converging at least from about two decades. The liberalization of the labor market will therefore accelerate an integration process already in action. This paper presents evidence on this process, based on the characteristics of the trans-border labor market (wage differentials, mobility, skills) and indicators on both supply and demand side of this specific regional market.
Keywords: 330